Subcutaneous vs Intravenous Heparin in the Treatment of Deep Venous Thrombosis – A Randomized Clinical Trial - Pini, M; Pattacini, C; Quintavalla, R; Poli, T; Megha, A; Tagliaferri, A; Manotti, C; Dettori, A G (Thrombosis and Haemostasis, 1990)
271 patients with acute symptomatic deep venous thrombosis of lower limbs, confirmed by strain-gauge plethysmography and/ or venography, were randomly assigned to receive intermittent subcutaneous heparin calcium or heparin sodium by continuous intravenous infusion for 6–10 days. Heparin dosage was adjusted to maintain activated partial thromboplastin time values (Throm-bofax reagent) at 1.3–1.9 times the basal ones. Strain-gauge plethysmography was repeated at the end of heparin treatment, and evaluation of therapy was performed by comparing the indexes of venous hemodynamics and by assessing the incidence of pulmonary embolism and of bleeding complications.In the intravenous group, Maximal Venous Outflow (MVO) increased from 20.8 ± 12.8 to 28.4 ± 17.5 ml/min per 100 ml of tissue and Venous Capacitance (VC) from 1.39 ± 0.92 to 1.94 ± 1.0 ml/100 ml of tissue (mean ± SD). In the subcutaneous group, MVO increased from 21.0 ± 12.7 to 27.5 ± 18.1 and VC from 1.60 ± 0.86 to 2.06 ± 1.0. The median improvement of MVO and VC were 22% and 36% respectively in the IV group and 20% and 24% in the SC group. Clinical pulmonary embolism occurred in 2 patients in the intravenous group (1 fatal) and in 4 in the subcutaneous group (1 fatal). 9 major bleeding complications occurred in the intravenous group (1 fatal) and 5 in the subcutaneous group (1 fatal). The differences were not significant at the statistical analysis.The results suggest that subcutaneous intermittent heparin has a comparable efficacy to continuous intravenous heparin in the treatment of deep venous thrombosis.To the same conclusion points an overview of the seven randomized trials which compared these treatment modalities.